2021
DOI: 10.3389/fmed.2021.660580
|View full text |Cite
|
Sign up to set email alerts
|

Go Ask Your Patients! PSS-QoL Reported Perception of Dryness Correlates With Lacrimal and Salivary Flow in Primary Sjögren's Syndrome

Abstract: Introduction/Objectives: The patient perspective is an essential outcome parameter in the quest for effective therapy in primary Sjögren's Syndrome (PSS). The EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) is recommended by EULAR to quantify patient's symptom burden and has been used in several clinical trials. Surprisingly, the patient's perception of dryness quantified with ESSPRI does not correlate with objective measures of salivary or lacrimal flow. Thus, we evaluated a newly developed assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Despite previous results showing weak association between subjective symptoms and objective testing for dry mouth, 32 other more recent studies have shown that patients' perception of dryness correlates with objective measurements of salivary gland function, including when it is assessed by XI. 10,33 These controversial results could be due the difficulties in assessing individual perception. 33 Moreover, median UWSF was lower among patients with a FS of 3 and 4 than among patients with a FS of 0 to 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous results showing weak association between subjective symptoms and objective testing for dry mouth, 32 other more recent studies have shown that patients' perception of dryness correlates with objective measurements of salivary gland function, including when it is assessed by XI. 10,33 These controversial results could be due the difficulties in assessing individual perception. 33 Moreover, median UWSF was lower among patients with a FS of 3 and 4 than among patients with a FS of 0 to 2.…”
Section: Discussionmentioning
confidence: 99%
“…10,33 These controversial results could be due the difficulties in assessing individual perception. 33 Moreover, median UWSF was lower among patients with a FS of 3 and 4 than among patients with a FS of 0 to 2. These findings are different than previous studies that showed no significant association between the degree of inflammation (FS) and hypofunction of the salivary glands, and reinforce the importance of FS as criteria for the diagnosis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between increasing ESSPRI scores and a decrease in non-stimulated total salivary flow has been reported in the literature [ 34 ]. Interestingly, ESSPRI dryness did not correlated with tear or salivary flow, but ESSPRI pain did [ 35 ]. Therefore, the authors noted that the ESSPRI dryness score may not reflect the true assessment of dryness [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ESSPRI dryness did not correlated with tear or salivary flow, but ESSPRI pain did [ 35 ]. Therefore, the authors noted that the ESSPRI dryness score may not reflect the true assessment of dryness [ 35 ]. In contrast, a more complex relationship and a more general concept of dryness under the influence of pain and fatigue should be assumed [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation